PERAN TEKNOLOGI DALAM MEMODERASI PENGARUH MODAL DAN TENAGA KERJA TERHADAP PRODUKSI PADA INDUSTRI KERAJINAN KERANG DI KABUPATEN BADUNG - Pratiwi, Wayan Lia Indah; Marhaeni, A A IN (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2021)
Economic sectors in Bali Province are experiencing rapid growth, one of that is shell craft industry which is one of the handicraft industries in Badung Regency. The objectives of this study were 1) to simultaneously analyze the effect of capital, labor and technology on the production of the shellfish craft industry in Badung Regency. 2) To partially analyze the effect of capital and labor on the production of the shell craft industry in Badung Regency. 3) Analyzing the role of technology in moderating the influence of capital and labor on the production of the shellfish handicraft industry in Badung Regency. The population of this research is 539 business units in 6 districts. 84 samples were taken through the Slovin formula which was taken randomly using stratified random sampling. The analysis technique used is the moderation regression analysis technique. Based on the results of the simultaneous analysis, capital, labor and technology have a significant effect on the production of the shellfish industry in Badung Regency. Partially, capital and labor have a significant positive effect on the production of the shellfish industry in Badung Regency. It was also found that companies that utilize modern technology have a production value that is not higher than companies that do not utilize modern technology. In the moderation test, the results show that there is a positive interaction of technology in moderating the influence of capital and labor on the production of the shellfish craft industry in Badung Regency